The components of career capital and how they are acquired by knowledge workers across different industries - M. Sutherland; G. Naidu; S. Seabela; S. Crosson (South African Journal of Business Management, 2015)
The literature shows that the way in which knowledge workers manage their careers in the global economy has changed fundamentally in the last twenty years. Career capital is a tradable commodity between and within organisations which impacts both human resource managers and knowledge workers. There is insufficient empirical evidence of the components of career capital and how these are acquired and there has been a dearth of investigation as to whether career capital is managed differently in different industries. The research was conducted in two phases. The first qualitative phase via 21 in-depth interviews identified 27 components of career capital and 23 methods of career capital accrual. In phase two quantitative data was collected, using those constructs, from 200 knowledge workers in four sectors: the public service sector and in manufacturing, financial and high tech research and development industries. The research determined the most important career capital components and methods of their accrual and showed these to differ greatly between the four employment sectors. The data raises questions with regard to two important themes in the career literature.
Keywords: 650